Financial reporting - Alexander, David; Britton, Ann. (London ; Melbourne : International Thomson Business Press, 1999)
This book is divided into three parts: The conceptual framework; The legal framework; and The regulatory framework about Financial reporting.
Keywords: Accounting; Finance; Accounting; Financial statements; Accounting -- Law and legislation